Rice husk-based hierarchical porous carbon for high performance supercapacitors: The structure-performance relationship. (May 2020) - Chen, Zhimin; Wang, Xiaofeng; Xue, Beichen; Li, Wei; Ding, Zhiyao; Yang, Xiaomin; Qiu, Jieshan; Wang, Zichen
Abstract: Rice husk-based hierarchical porous carbon (RHPC) has great promising applications in supercapacitors. Herein we systematically examined the formation mechanism of hierarchical porous structure of RHPC, tried to work out the intrinsic relationship of pore structure and the electrochemical performance. A method for separation of components in rice husk is proposed. It has been found that the pore structure in RHPC is closely related to different components in rice husk, and can be tuned by carbonization, desiliconization, and activation, shedding a light on the formation mechanism of the hierarchical porous structure in RHPC. The electrochemical performance of RHPC and the porous carbons made from three rice husk components has been correlated to their porous structure. The micropores function to provide a large number of adsorption sites for electrolyte ions, leading to high specific capacitance, while the mesopores coupled with the macropores function to provide fast transport channels for electrolyte ions, which play the key role for the excellent rate capability of RHPC. The stable skeleton structure with good conductivity ensures the superior cycling stability of RHPC. Graphical abstract: Via a detailed component separation method, the pore source, the formation mechanism of hierarchical porous structure, and the structure-performance relationship of RHPC are determined. Image 1